Pengembangan Modul Pembelajaran Ekonomi Berbasis Reflektif Inkuiri Pada Materi Pajak Kelas XI Madrasah Aliyah Swasta Nurul Hidayah Bengkalis - Selsa dharma Wulan; Fitriani Fitriani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
This study has the following objectives: (1) Designing and developing an economic learning module based on reflective inquiry (social inquiry) as an economics module for class XI Madrasah Aliyah Swasta Nurul Hidayah. (2) Produce products, namely innovative learning modules for students. (3) Seeing the quality and feasibility of the reflective inquiry-based module (social inquiry) as a guide for economic learning.Research on the development of an inquiry-based reflective economic learning module on this tax material uses the Research And Development (R&D) research method that has been developed by Sugiyono, namely: (1) Potential and Problems. (2) Gathering Information. (3) Product Design. (4) Design Validation. (5) Design Improvements. (6) Product Trial. (7) Product Revision. (8) Trial of Use. (9) Product Revision. (10) Production of Mass Products. Based on the validation by material experts obtained 80.3% results in the very feasible category, media validation by the first media expert obtained 88% results in the very feasible category, the second media expert obtained 89.1% results in the very feasible category, and lastly were students the results obtained are 92.4% with a very interested category. With the conclusion that this learning module is suitable for use in the learning process. DOI: https://dx.doi.org/10.17977/UM014v15i12022p065